2018
DOI: 10.3389/fgene.2018.00689
|View full text |Cite|
|
Sign up to set email alerts
|

Caveolin-1 Variant Is Associated With the Metabolic Syndrome in Kuwaiti Children

Abstract: Caveolin-1 (CAV1) variants have been suggested to be associated with obesity and related metabolic disorders, but information based on human studies is limited. In the present study, we aimed to investigate the potential association between the CAV1 rs1997623 C/A variant and metabolic syndrome (MetS) in Kuwaiti children. DNA from saliva samples collected from 1313 Kuwaiti children (mean age: 12 years) were genotyped using the TaqMan SNP genotyping assay. The classification of MetS was based on the presence/abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
5
13
0
Order By: Relevance
“…To the authors' knowledge, there is little evidence describing an association between Cav-1 and metabolic syndrome. It was observed that a genetic variant of Cav-1 (rs3807992) was associated with increased MetS risk, which is consistent with previous studies that revealed a signi cant association between the minor allele in cav-1 variations and the odds of metabolic diseases 10,11,15,17 . Also, compared with other candidate gene studies, no studies had evaluated SNP rs3807992 and MetS risk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To the authors' knowledge, there is little evidence describing an association between Cav-1 and metabolic syndrome. It was observed that a genetic variant of Cav-1 (rs3807992) was associated with increased MetS risk, which is consistent with previous studies that revealed a signi cant association between the minor allele in cav-1 variations and the odds of metabolic diseases 10,11,15,17 . Also, compared with other candidate gene studies, no studies had evaluated SNP rs3807992 and MetS risk.…”
Section: Discussionsupporting
confidence: 90%
“…The exact mechanisms are unclear, but it seems that Cav-1 is able to regulate several key enzymes in lipid metabolism, such as cholesterol ester transfer protein and phospholipid transfer protein 13 . While the association between Cav-1 polymorphisms and type 2 diabetes risk has been widely reported in various populations 14 , these relationships with MetS have been inconsistent, despite several publications on the association between Cav-1 gene variants and serum lipid pro les [14][15][16][17] . To the authors' knowledge, there has been no study evaluating Cav-1 rs3807992 variant, metabolic risk factor, and the interaction of fatty acid intake levels with this SNP.…”
Section: Introductionmentioning
confidence: 99%
“…CAV1 SNP variants have been suggested to be linked to metabolic syndrome (MetS), a major risk factor for diabetes and coronary artery disease. Several CAV1 single-nucleotide polymorphisms (SNP) were found to associate with MetS: rs926198 in Caucasians and Hispanics [77], rs3807989 in the Chinese Han population [78], and rs1997623 in Kuwaiti children as shown by our previous study [79]. The forest plot in Figure 3 shows an association between LHDLC and MetS with the heterozygous genotype CA and the A-allele, meaning that a carrier of the A genotype has a higher chance of developing MetS in the studied population.…”
mentioning
confidence: 61%
“…Caveolin-1 has been reported to regulate metabolism of lipid droplets in adipocytes (Briand et al, 2014, reviewed in Martin, 2013 and endothelial cells (Kuo et al, 2018), including the composition in peripheral phospholipids and associated proteins (Blouin et al, 2010). CAV-1 gene polymorphisms have been reported in patients with altered lipid metabolism in adult (Mora-Garcia et al, 2017 and juvenile forms (Nizam et al, 2018). Metabolic alterations are partially mediated by impaired insulin signaling (Gonzalez-Munoz et al, 2009;Perez-Verdaguer et al, 2018;Travez et al, 2018).…”
Section: Traffic Of Macromolecules and Metabolic Regulationmentioning
confidence: 99%